2017
DOI: 10.1002/adfm.201703171
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Porous Electrodes by Design: Toward Enhancing the Effective Utilization of Platinum in Electrocatalysis

Abstract: 2Platinum nanoparticle functionalized ordered porous support electrodes are prepared and characterized as a potential new class of oxygen reduction reaction (ORR) electrocatalysts.This study aims to develop electrode materials that enhance the effective utilization of Pt in electrocatalytic reactions through improved mass transport properties, high Pt mass specific surface area, and increased Pt electrochemical stability. The electrodes are prepared using modular sacrificial templates, producing a uniform dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 63 publications
0
15
0
1
Order By: Relevance
“…Hierarchial scaffolds, having both nano- and microporosity, are particularly valuable for their ability to maintain a high surface area for applications such as electrochemical energy storage (EES) and electrocatalysis. Inverse opaline structures (also known as 3D ordered macroporous, 3DOM, structures) have recently been highlighted in the literature for use as cathodes for EES and electrocatalysis technologies because of their near ideality in several design aspects; namely, the 3DOM structures are fully bicontinuous and may be hierarchical in nature, using a solid template to create the macropores and either nanoparticles (NPs) or porous infiltration of the solid template to generate nanoscale features. , The main drawback of the 3DOM structures is their reliance on templating and the existence of constrictions between pores, which may negatively impact effective mass transport and increases diffusion lengths. In order to improve on 3DOM structures, bicontinuous materials prepared via spinodal decomposition routes are desirable.…”
mentioning
confidence: 99%
“…Hierarchial scaffolds, having both nano- and microporosity, are particularly valuable for their ability to maintain a high surface area for applications such as electrochemical energy storage (EES) and electrocatalysis. Inverse opaline structures (also known as 3D ordered macroporous, 3DOM, structures) have recently been highlighted in the literature for use as cathodes for EES and electrocatalysis technologies because of their near ideality in several design aspects; namely, the 3DOM structures are fully bicontinuous and may be hierarchical in nature, using a solid template to create the macropores and either nanoparticles (NPs) or porous infiltration of the solid template to generate nanoscale features. , The main drawback of the 3DOM structures is their reliance on templating and the existence of constrictions between pores, which may negatively impact effective mass transport and increases diffusion lengths. In order to improve on 3DOM structures, bicontinuous materials prepared via spinodal decomposition routes are desirable.…”
mentioning
confidence: 99%
“…Even though the self-supported Pt–CoO achieved a high activity and ECSA, the full cell performance was not achieved. Gates et al have discussed the impact from the porosity and utilization of the Pt catalyst on the cell performance . They constructed mesoporous platinum by the electrodeposition method and found that mesoporous platinum exhibited an improved mass specific power density compared to the commercial Pt/C catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Gates et al have discussed the impact from the porosity and utilization of the Pt catalyst on the cell performance. 11 They constructed mesoporous platinum by the electrodeposition method and found that mesoporous platinum exhibited an improved mass specific power density compared to the commercial Pt/C catalyst. In their result, the higher performance can be contributed to the easy ionic and mass transportation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, the ordered array of porous structure can facilitate mass transfer. [45][46][47] Furthermore, the frameworks can be readily and softly modified by means of chemical methods. [48][49][50] The hard template method is a powerful tool for producing carbon materials with precisely controlled structures at the nanometer level, which would be comparable to other chemical and physical methods.…”
Section: Introductionmentioning
confidence: 99%